Neural Correlates of Syntax and Proto-Syntax: Evolutionary Dimension - Progovac, Ljiljana; Rakhlin, Natalia; Angell, William; Liddane, Ryan; Tang, Lingfei; Ofen, Noa (Frontiers in Psychology, 2018)
The present fMRI study tested predictions of the evolution-of-syntax framework which analyzes certain structures as remnants (“fossils”) of a non-hierarchical (non-recursive) proto-syntactic stage in the evolution of language (Progovac 2015, 2016). We hypothesized that processing of these structures, in comparison to more modern hierarchical structures, will show less activation in the brain regions that are part of the syntactic network, including Broca’s area (BA 44 and 45) and the basal ganglia, i.e., the network bolstered in the line of descent of humans through genetic mutations that contributed to present-day dense neuronal connectivity among these regions. Fourteen healthy native English-speaking adults viewed written stimuli consisting of: 1) full sentences (e.g. The case is closed); 2) Small Clauses (e.g. Case closed); 3) Complex hierarchical compounds (e.g. joy-killer); 4) Simple flat compounds (e.g. kill-joy). Small Clauses (compared to full sentences) resulted in reduced activation in the left BA 44 and right basal ganglia. Simple (relative to complex) compounds resulted in increased activation in the inferior temporal gyrus and the fusiform gyrus (BA 37/19), areas implicated in visual and semantic processing. We discuss our findings in the context of current theories regarding the co-evolution of language and the brain.